Exergy analysis of process heaters. (4th June 2010) - Sahin, Ahmet Z.; Zubair, Syed M.
A thermodynamic analysis is proposed to investigate the entropy generation in process heaters. It is found that the major portion of the exergy losses occur in the stack. It is also found that the excess air decreases the first law efficiency while the second law efficiency remains nearly constant. Although the first law efficiency is found to be of the order of 70-90%, the second law efficiency has been calculated to be low, in the range of 30-40%. In this regard, stack gas temperature is found to be an important parameter for improving the second law efficiency.